Self‐Assembly‐Driven Electrospinning: The Transition from Fibers to Intact Beaded Morphologies. Issue 15 (2nd June 2015) - Wang, Linge; Topham, Paul D.; Mykhaylyk, Oleksandr O.; Yu, Hao; Ryan, Anthony J.; Fairclough, J. Patrick A.; Bras, Wim
<x xml:space="preserve">Abstract</x> Polymer beads have attracted considerable interest for use in catalysis, drug delivery, and photonics due to their particular shape and surface morphology. Electrospinning, typically used for producing nanofibers, can also be used to fabricate polymer beads if the solution has a sufficiently low concentration. In this work, a novel approach for producing more uniform, intact beads is presented by electrospinning self‐assembled block copolymer (BCP) solutions. This approach allows a relatively high polymer concentration to be used, yet with a low degree of entanglement between polymer chains due to microphase separation of the BCP in a selective solvent system. Herein, to demonstrate the technology, a well‐studied polystyrene‐poly(ethylene butylene)–polystyrene triblock copolymer is dissolved in a co‐solvent system. The effect of solvent composition on the characteristics of the fibers and beads is intensively studied, and the mechanism of this fiber‐to‐bead is found to be dependent on microphase separation of the BCP.